Boom, bust, action! How communities can cope with boom‐bust cycles in unconventional oil and gas development. Issue 5 (26th June 2022) - Arnold, Gwen; Klasic, Meghan; Schomburg, Madline; York, Abigail; Baum, Melissa; Cherin, Maia; Cliff, Sydney; Kavousi, Parisa; Miller, Alexandria Tillett; Shajari, Diana; Wang, Yuer; Zialcita, Luigi
Abstract: Scholarship on boom‐busts cycles in resource extraction often assumes that affected resource‐rich communities are at best reactive, at worst helpless, in the face of the large, exogenous shocks this cycle visits upon them. Researchers infrequently examine what communities themselves can do to improve their economic prospects and residents' quality of life amidst booms and busts. In this review paper, we identify and synthesize work scattered across disparate academic and gray literature—in planning, law, community economic development, rural sociology, economics, and political science, among others—to holistically assess what we know about how communities can use local policymaking to manage impacts of booms and busts associated with unconventional oil and gas drilling (UOGD), often called "fracking." We highlight examples of communities tackling this task using vertical and horizontal governance strategies and distill expert recommendations for how communities can build boom‐bust resiliency generally and in key areas impacted by UOGD. Resumen: Los estudios sobre los ciclos de auge y caída en la extracción de recursos a menudo asumen que las comunidades ricas en recursos afectadas son, en el mejor de los casos, reactivas, y en el peor, indefensas, frente a los grandes impactos exógenos que este ciclo les ocasiona. Los investigadores examinan con poca frecuencia lo que las propias comunidades pueden hacer para mejorar sus perspectivas económicas y la calidad de vida de los residentes en medio de auges y caídas. En este documento de revisión, identificamos y sintetizamos el trabajo disperso en literatura académica y gris dispar, en planificación, derecho, desarrollo económico comunitario, sociología rural, economía y ciencias políticas, entre otros, para evaluar de manera integral lo que sabemos sobre cómo las comunidades pueden usar formulación de políticas locales para gestionar los impactos de los auges y caídas asociados con la perforación no convencional de petróleo y gas (UOGD), a menudo llamado "fracking". Destacamos ejemplos de comunidades que abordan esta tarea utilizando estrategias de gobernanza vertical y horizontal y destilamos recomendaciones de expertos sobre cómo las comunidades pueden desarrollar resiliencia en general y en áreas clave impactadas por UOGD. 摘要: 关于资源开采方面的繁荣‐萧条周期的学术研究通常假设，受影响的资源丰富社区在面对该周期对其造成巨大的外部冲击时，其最好的情况是采取响应，而最坏的情况则是无能为力。研究人员很少分析社区自身在繁荣和萧条期间能做些什么来改善其经济前景和居民的生活质量。在本篇综述中，我们识别并综合了不同学术文献和灰色文献——包括规划、法律、社区经济发展、农村社会学、经济学和政治学等领域——以全面评估社区如何能使用地方政策决策来管理与"非常规石油天然气钻探"(UOGD，通常被称为"水力压裂")相关的繁荣与萧条的影响。我们重点介绍了使用纵向和横向治理策略解决该任务的社区案例，并提炼了有关"社区如何在受UOGD影响的关键领域建立繁荣‐萧条复原力"的专家建议。